Macroeconomic Determinants of Stock Market Development in Sample African Economies - Ayoub, Ehab (AUC Knowledge Fountain, 2023)
This research paper studies the relationship between macroeconomic determinants as independent variables and different measures of stock market development as dependent variables across selected emerging economies in Africa for the period of 2002 to 2021, with a quarterly frequency using time series analysis. The independent variables used are Core Inflation, Deposit Rate, Foreign Direct Investment (FDI), FX Rate against USD, Domestic Credit, Gross Domestic Product (Real GDP), Exports, Imports, External Debt, and Foreign Reserves. We use these variables as our main determinants of measuring economic growth. With regards to stock market development, we use four proxy measures as our benchmark, which includes, Index Return, Market Capitalization, Volume Traded and Value Traded. The methodology used was the Vector Error Correction Model (VECM), which is a multivariate model, which is derived from the Vector Autoregressive Model (VAR). We test for stationarity and cointegration among the variables using the Augmented Dickey Fuller Test and Johansen Cointegration Test. The selected African nations are made up of four diverse yet similar countries, comprising of Egypt, Morocco, Nigeria and South Africa. The main objective of this proposal is to analyze stock markets across these emerging markets, in which we can enhance the overall scheme of this platform using key macroeconomic factors. The macroeconomic factors are tailored to mutual challenges, such as trade deficit, current account deficit, high inflationary economies, poor debt management and unsteady source of foreign currency. Our results in each country were different, however there is a long-term unidirectional relationship between specific macroeconomic variables and the stock market development in each country, despite that there may have been no short-term relationships shown.